Salas de recursos multifuncionais: contexto de Inclusão Escolar para os alunos público-alvo da Educação Especial ? - Silva, Suzana Sirlene da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study is linked to a proposal of integrated research selected in a public notice from Proesp/Capes (2019/2009) entitled Implementation of a Specialized Educational Service Center in Araraquara Municipality: Quality Indicator Survey. It arose from the following study matters: in which ways have the acquisition and development of academic learning by pupils with disability and global development disorders or high ability/gifted students been enabled in the context of Multifunctional Resource Rooms (SRMs) in the researched municipality? Which challenges and possibilities has this proposal of service presented for the School Inclusion of its target group? The study's general goal was to identify and to describe the service structure and the pedagogical work developed in the SRMs. Its specific goal was to characterize the Multifunctional Resource Room, the specialized teachers, some information about the students assisted and the possible relationships of collaboration between the specialized and the regular classroom teachers from the perspective of Special Education. It consisted of an investigation with descriptive nature and qualitative approach. The data collection instruments were: structured non-participative observation and mixed questionnaire with open and closed-ended questions. The categorization by content analysis was used to analyze data. The observations took place in two SRMs implemented in school units. The research participants were teachers specialized in Special Education working in the Municipal Education Network studied. The pedagogical work of three of them was observed. The results revealed that the Municipal Network has a specialized teachers team with proper training to act in the area, which often attends continuing training courses and has previous experience in Special Education. It also has multifunctional resource rooms equipped with didactic-pedagogical and technological material and furniture provided by ...

Esse estudo está vinculado a uma proposta de pesquisa integrada, selecionada em Edital Proesp/Capes (2019/2009), intitulada Proposta de Implantação de Núcleo de Atendimento Educacional Especializado no Município de Araraquara: levantamento de indicadores de qualidade. Partiu das seguintes questões de estudo: Como tem sido oportunizado a aquisição e o desenvolvimento da aprendizagem acadêmica dos alunos com deficiência, transtornos globais do desenvolvimento e altas habilidades/ superdotação no contexto de Salas de Recursos Multifuncionais no município pesquisado? Quais os desafios e possibilidades que esta proposta de atendimento tem apresentado para a Inclusão Escolar de seu público alvo? O estudo teve por objetivo geral identificar e descrever a estrutura de atendimento e o trabalho pedagógico desenvolvido em S.R.M. e, por objetivo específico a pesquisa buscou caracterizar a Sala de Recursos Multifuncionais, os professores (as) especialistas, os alunos atendidos e as possíveis relações de colaboração existentes entre o professor especialista e o professor de sala regular sob a optica da profissional da Educação Especial. Constituiu-se em uma investigação com abordagem qualitativa, de natureza descritiva e o uso dos instrumentos de coleta de dados: observação estruturada não participante e questionário misto com questões abertas e fechadas. Para analisar os dados, foi utilizado categorização de análises de conteúdos. O local das observações foram duas S.R.M. implantadas em 2 unidades escolares. As participantes da pesquisa foram as professoras especialistas em Educação Especial atuantes na Rede Municipal de Educação pesquisada, sendo que 3 dessas professoras tiveram o trabalho pedagógico observado. Os resultados revelaram que a Rede Municipal conta com equipe de professores especialistas que tem formação adequada para atuar na área, frequentando constantemente cursos de formação continuada ...
Keywords: Educação; Educação especial; Inclusão em educação; Professores de educação especial; Special education